2004
DOI: 10.1590/s0100-879x2004000700003
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of erythrocyte-conjugated dienes indicate increased lipid peroxidation in schistosomiasis mansoni patients

Abstract: Schistosoma mansoni causes liver disease by inducing granulomatous inflammation. This favors formation of reactive oxygen species, including superoxide ions, hydrogen peroxide and hydroxyl radicals all of which may induce lipid peroxidation. We have evaluated lipid peroxidation in 18 patients with hepatosplenic schistosomiasis mansoni previously treated with oxamniquine followed by splenectomy, ligature of the left gastric vein and auto-implantation of spleen tissue, by measuring levels of erythrocyte-conjugat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 15 publications
2
6
0
Order By: Relevance
“…In accord with earlier findings of (Facundo et al 2004), who reported 10% increase of plasma indicator MDA concentration in 18 patients with mansoni schistosomiasis, treated surgically by splenectomy, when compared to control group, but statistically couldn't show significant rise. This may be explained due to limited number of cases.…”
Section: Discussionsupporting
confidence: 91%
“…In accord with earlier findings of (Facundo et al 2004), who reported 10% increase of plasma indicator MDA concentration in 18 patients with mansoni schistosomiasis, treated surgically by splenectomy, when compared to control group, but statistically couldn't show significant rise. This may be explained due to limited number of cases.…”
Section: Discussionsupporting
confidence: 91%
“…Regarding the significant increase in the TBARS/MDA in the test group, it was observed that these data were also reported in other papers, which show an association between the Schistosoma mansoni and high levels of reactive substances to thiobarbituric acid (TBARS) and reactive oxygen species (ROS) (Facundo et al 2004;Del Rio et al 2005;Eboumbou et al 2005). In man, infection with S. mansoni is associated with increased levels of circulating TBARS and ROS adducts (Pascal et al 2000).…”
Section: Discussionsupporting
confidence: 82%
“…Unsaturated hydroxyalkenal 4-HNE can be investigated in tissues, preferably using immunohistochemistry (IHC), or HPLC [82, 83]. CDs, produced as a consequence of free radical-induced autoxidation of polyunsaturated fatty acids (PUFAs), can be detected according to Suryanarayana Rao and Recknagel, which follows the maximal absorption of UV light at 233 nm by these compounds [8486]. Finally, LOOHs, which are the primary oxidation products of PUFAs, can be determined by the ferrous oxidation xylenol orange (FOX) assay, based on the ability of LOOH to oxidize ferrous iron in the presence of xylenol orange, leading to the formation of a colored ferric-xylenol orange complex, with an absorbance at 560 nm [87, 88].…”
Section: Methods and Approaches To Measure Oxidative Stress In CLImentioning
confidence: 99%